Analysis of Student Discipline Factors (Case Study at IDIA Prenduan Sumenep in 2022) - Afifah, Afifah; Fitrianingsih, Fitrianingsih (Penerbit Hellow Pustaka, 2025)
Discipline in an educational institution is an element that is very much needed as well as the most effective means in the learning process. A disciplined attitude provides many benefits to maintain a balance between the tendency and desire of children to do something with the regulations needed in the environment. And efforts that can be made in instilling a disciplined attitude in children are to provide good examples and habits for actions carried out every day. This study focuses on the discipline of female students and the supporting and inhibiting factors of the discipline of female students at IDIA Prenduan Sumenep. This study uses descriptive qualitative research with a case study research type. The data sources in this study were obtained from leaders, naibah, ustadzah and female students. using interview and observation methods. From this method, the researcher analyzed the data and information obtained from informants, by reducing data, presenting data and finally concluding it so as to produce information that is in accordance with the focus of the study. The discipline applied in the IDIA environment is divided into 3 parts, namely the Sharia field (worship) such as congregational prayer, tahajjud prayer, tadarus muajjah and other worship activities. The language field such as female students must use the official language (English and Arabic) as their daily language, and the qonun field (orderly clothing that can be used both inside and outside the dormitory, and time to study. Supporting factors are the awareness that grows within female students, the character or personality that is formed within female students, motivation that can raise the spirit of female students, and the tazwidul mufrodat agenda. Inhibiting factors are inherited from home or bad behavior, lack of knowledge of nahwu and sorof, and wrong and socializing or wrong in choosing friends.